Complementarities between employee involvement and financial participation : Do institutional context, differing measures, and empirical methods matter? - Jones, Derek C.; Kalmi, Panu; Kato, Takao; Mäkinen, Mikko (SAGE Publishing, 2016)
While most studies on complementarities are for the US and the UK, liberal market economies, we investigate whether productivity is greater if firms use employee involvement (EI) in decision-making and financial participation (FP) practices in tandem in a coordinated market economy. Representative data for Finnish manufacturing firms are used. Our diverse specifications reflect varying approaches in theoretical and empirical work on complementarities. Using panel data and looking at the incidence of various EI and FP practices (the extensive margin), we find next to no evidence in support of complementarities. However, we find some evidence for such complementarities using cross sectional data (where we control for several covariates that related work has found to be important for firm performance), and also when we focus on the intensity of FP (the intensive margin). In accounting for differences in empirical findings across varying settings, our findings suggest a role for institutional context and that differing measures and empirical methods matter.
Keywords: new workplace practices; employee involvement; financial participation; complementarities; HRM; firm productivity; fi=Taloustiede|en=Economics|